If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g + -27 = 2 * 45 Reorder the terms: -27 + g = 2 * 45 Multiply 2 * 45 -27 + g = 90 Solving -27 + g = 90 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + g = 90 + 27 Combine like terms: -27 + 27 = 0 0 + g = 90 + 27 g = 90 + 27 Combine like terms: 90 + 27 = 117 g = 117 Simplifying g = 117
| 3n^2-10n-8=0 | | 3n^2-13n+4=0 | | 3n^2-13+4=0 | | 6x-27-50=7 | | 4xy(3yz)(-5xz)= | | 7*6=3t | | x^2+3=4x+35 | | 8x-16= | | 2x^2-12x+7=5 | | 0.45(6)+0.05x=0.15(24+x) | | 4X=6x^2 | | (2a-1)((4a)(4a)+2a+1)= | | 9(t-6)+6t=5(3t+2)-8 | | 0.25(10000)-0.04y=0.06(y+10000) | | -150=-5(-5b) | | -3y=6 | | 4(2y-1)-(2y)=6 | | x^2+9=8x | | (12y+5)(12y-5)= | | 2+2x+2=46 | | 5-5=16s-12s | | 3x(2x-1)=1 | | 42=-2x+6 | | (8p^3+3p^2-4)+(6p^3-3p+5)= | | 2(3x-8)=38 | | -16=-2a+7(5-7a) | | 6x-10=68 | | -77=7(-8x-3) | | y-4(2)=0 | | 8=-4(-8n-2) | | -3(-8-6b)=6 | | 61=-5(1-8v)-7v |